Evaluation of Sustainability Large Pelagic Fisheries In Morotai Island District - M. Abdullah, Rommy; Taeran, Imran; Irham, Irham; H. Iksan, Kusdi (Agrikan Jurnal Agribisnis Perikanan, 2022)
This study aims to measure and determine the sustainability status of large pelagic fisheries in a sustainability perspective according to ecological, economic, social, technological, and legal/institutional dimensions in Morotai Island District. The method used in this study is a survey method and quantitative descriptive with analytical tools, namely RAPFISH analysis. Based on the analysis, the sustainability of the ecological and legal and institutional dimensions of large pelagic fisheries has a moderately sustainable status (range 50-75), with an average sustainability index value of 55.79. The economic, social and technological dimensions have a less sustainable status (range 25-50), while the legal and institutional dimensions have a good sustainability status (range 75-100) and the ecological dimension has a fairly sustainable status (range 50-75). The attributes that have the most influence (sensitive) on the sustainability status of large pelagic fisheries based on the five dimensions above are the level of collapse and pre-maturity of catch (ecology), employment and other income (economy), new entrants to fisheries and family participation (social). , is an attribute of pre-sale processing and use of FAD'S (technology), and illegal fishing and the availability of law enforcement personnel (legal and institutional).